2020
DOI: 10.1186/s13027-020-0273-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features and outcomes between HBV-related and non-B non-C hepatocellular carcinoma

Abstract: Objective: To evaluate the difference between hepatitis B virus related hepatocellular carcinoma (HBV-HCC) and non-HBV non-HCV hepatocellular carcinoma (NBNC-HCC) patients based on clinical features and prognosis. Methods: A total of 175 patients with HCC were enrolled. Patients' characteristics were extracted from medical records. Among them, 107 patients were positive for HBsAg and negative for HCV-Ab while 68 patients were negative for HBsAg and HCV-Ab. Results: The patients in the NBNC-HCC group were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The patients with HBV-HCC were younger, less frequently had T2DM or hypertension, had a lower BMI, and were more likely to have liver cirrhosis, capsule invasion, and vascular invasion. The results of a Japanese study support our findings ( 48 ): Xue et al. confirmed that patients with HBV-HCC were younger and more likely to have vascular invasion compared to patients with NBNC-HCC.…”
Section: Discussionsupporting
confidence: 89%
“…The patients with HBV-HCC were younger, less frequently had T2DM or hypertension, had a lower BMI, and were more likely to have liver cirrhosis, capsule invasion, and vascular invasion. The results of a Japanese study support our findings ( 48 ): Xue et al. confirmed that patients with HBV-HCC were younger and more likely to have vascular invasion compared to patients with NBNC-HCC.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with HBV-related HCC are defined as those who are seropositive for hepatitis B surface antigen (HBsAg), are seronegative for anti-HCV antibodies and have no history of alcoholism [ 3 ]. China's HBV-related HCC incidence and mortality rates are higher than the world average [ 4 , 5 ]. HCC associated with HBV is heterogeneous, with a wide range of clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, Riordan et al [9] displayed that no significant association was detected between FIGN mRNA expression and survival of HCC patients in America. A series of outcomes comparison between HBV related HCC (HBV-HCC) and non-HBV non-HCV HCC (NBNC-HCC) revealed that HBV-HCC patients had significantly shorter OS and DSF [23][24][25]; while postoperative regular antiviral therapy could prolong survival the HCC patients with baseline higher HBV DNA titter [26]. Above evidence indicate that HBV infection is an independent risk for adverse outcome in HCC patients.…”
Section: Discussionmentioning
confidence: 99%